2009
DOI: 10.1242/jeb.029918
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic temperature affects muscle fibre recruitment in adult zebrafish: genome-wide changes in gene and microRNA expression associated with the transition from hyperplastic to hypertrophic growth phenotypes

Abstract: SUMMARYWe investigated the effects of embryonic temperature (ET) treatments (22, 26 and 31°C) on the life-time recruitment of fast myotomal muscle fibres in zebrafish Danio rerio L. reared at 26/27°C from hatching. Fast muscle fibres were produced until 25 mm total length (TL) at 22°C ET, 28 mm TL at 26°C ET and 23 mm TL at 31°C ET. The final fibre number (FFN) showed an optimum at 26°C ET (3600) and was 19% and 14% higher than for the 22°C ET (3000) and 31°C ET (3100) Supplementary material available online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 75 publications
3
122
0
5
Order By: Relevance
“…However, it remains unclear whether the changes in DNA methylation variation were specific to myog alone because methylation changes at other loci were not investigated. Johnston et al (2009) provided evidence that in addition to DNA methylation, microRNA expression at different embryonic temperatures can also be associated with the transition from hyperplastic to hypertrophic muscle growth phenotype in adult zebrafish (Danio rerio). Effects of microRNA on thermal plasticity are not only confined to simple developmental transitions, but have also been shown to be involved in complex neuronal network remodelling.…”
Section: Within-generational Epigenetic Effectsmentioning
confidence: 99%
“…However, it remains unclear whether the changes in DNA methylation variation were specific to myog alone because methylation changes at other loci were not investigated. Johnston et al (2009) provided evidence that in addition to DNA methylation, microRNA expression at different embryonic temperatures can also be associated with the transition from hyperplastic to hypertrophic muscle growth phenotype in adult zebrafish (Danio rerio). Effects of microRNA on thermal plasticity are not only confined to simple developmental transitions, but have also been shown to be involved in complex neuronal network remodelling.…”
Section: Within-generational Epigenetic Effectsmentioning
confidence: 99%
“…The influence of developmental temperature on the muscle ontogeny of the fish which has long been established (Johnston 1981(Johnston , 1993(Johnston , 2006Johnston et al 2009;Koumoundouros et al 2009) appears to have a substantial effect on swimming performance. Different temperatures lead to variation in body muscle mass (in terms of size and number of muscle fibres) that directly affect swimming ability.…”
Section: Discussionmentioning
confidence: 99%
“…Koumoundouros et al (2009), showed that in the case of European sea bass, the best swimmers had relatively higher red muscle to white muscle ratio and more red muscle fibres than the others. In the case of zebrafish, Johnston et al (2009) showed that the optimal embryonic temperature for fast muscle fibre recruitment (hyperplasia) is 26°C, as in that temperature there were 18.8% more fast fibers than at 22°C and 13.7% more fibers than at 31°C. After this phase, myotube formation stops and a new phase begins (hypertrophy) that consists of nuclear accretion and increase in fibre length and diameter (Johnston et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of Experimental Biology (2014) doi:10.1242/jeb.094037 size of both red fibres (Scott and Johnston, 2012) and fast glycolytic (white) fibres (Johnston et al, 2009) in zebrafish: fibres tend to be larger but fewer in number in fish raised at 22°C or 31-32°C as embryos compared with fish raised at 26-27°C. The observation that muscle COX and PK activities are higher in concert with an increase in muscle fibre size (but not total area) in the 22°C and 32°C T E groups provides correlative evidence that there may be metabolic consequences for the often observed effect of T E on muscle cellularity (Vieira and Johnston, 1992;Rowlerson and Veggetti, 2001;Stoiber et al, 2002;McClelland and Scott, 2013).…”
Section: Research Articlementioning
confidence: 99%